Implementasi Tools Mekatronikarobotik Education Berbasis Technology Education Smart Robot Mobile Transporter With Android Microcontroller Melalui Kegiatan Holiday Program Dalam Peningkatan Kompetensi Kreatif Dan Inovatif Membentuk Karakter Gen Z - Suherdi, Devri; rezky, syarifah; Saniman (Jurnal Masyarakat Indonesia (Jumas), 2025)
Education is one of the top efforts to combat ignorance and poverty, especially in our country, Indonesia. Whereas when that person attends school, they have already learned many things and gained insights into this world. Education can be obtained anytime and anywhere, therefore we as humans should be aware of this. In the future, education will have a significant impact on future development. Speaking of the future, in this industrial technology era, we are required to think ahead, especially now supported by various automation technologies such as AI and IoT. From this point, researchers want to share and show full concern for education that must keep up with the times by implementing the Holiday Program, which consists of teaching and learning activities for Gen Z high school/vocational school teenagers, utilizing media technology that currently dominates our education world. Robotics is a natural application of mechatronics, and integrating robotics into education can help students develop important skills in programming, engineering, and problem-solving. The smart mobile transporter robot with an Android microcontroller is a specific example of a mechatronic system that can be used in an educational context. The Android microcontroller is powerful and versatile, making it suitable for controlling complex systems like robots. By implementing this system in a workshop educational environment, students can gain hands-on experience with mechatronics and robotics concepts, while also developing important skills such as teamwork and collaboration. In addition to the technical skills that students can develop, this type of education can also help shape the character of Gen Z. By focusing on creative and innovative competencies, students can learn to think outside the box and develop problem-solving mindsets. This is an important skill in today's rapidly changing world, where new challenges and opportunities constantly arise. The Holiday Program is a field study to fill the holidays with beneficial activities that will be carried out by Gen Z students from schools or institutions to engage in learning activities conducted either within the school environment or outside the school (especially at Partner Collaboration Service Locations).